E agora, cara pálida? Educação e povos indígenas, 500 anos depois - Nietta Lindenberg Monte (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2000)
For almost 500 years, many indian nations have experimented processes of formal education. If in the past, school was imposed upon them, today their education is an important political issue among ethnic movements through out the continent, from wich a new juridical and institutional point of view has derived. In Brazil, alternative projects to prepare indian teachers have been inspiring government policies and have become a referential for the educational changes which are now taking place. These projects have brought about new partnerships, mechanism of participation and curriculum flexibility. But once the projects are embraced by the Government, they become matrices for unifier policies which tend to wipe out the diversity of indian nations and the different pedagogical approaches. The purpose of this article is to bring forth the improvements and the problems related to these educational processes